2019
DOI: 10.1016/j.healthpol.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

What drives hospital wards’ ambidexterity: Insights on the determinants of exploration and exploitation

Abstract: a b s t r a c tObjectives: Hospital wards are required to exploit current knowledge and explore for new knowledge. Ambidexterity (i.e., the capability to combine both exploitation and exploration) is a major issue in healthcare as result of the growing expectations that hospitals wards have the capability to manage the trade-off between high-quality delivery of care and cost-containment. This study sheds novel light on the determinants of ambidextrous behaviours in hospital wards. Methods: A theoretical framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The study advances knowledge through showing the role that human resource management practices can have in mediating the relationship between strategy and financial success. Previous research has mainly been confined to the marketing capability (O'Cass et al ., 2014), the hospitality industry (Foglia et al , 2019). Uniquely, we illustrate and position the importance of human resource management practices as an important organisational capability mediating the relationship between strategy and financial performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study advances knowledge through showing the role that human resource management practices can have in mediating the relationship between strategy and financial success. Previous research has mainly been confined to the marketing capability (O'Cass et al ., 2014), the hospitality industry (Foglia et al , 2019). Uniquely, we illustrate and position the importance of human resource management practices as an important organisational capability mediating the relationship between strategy and financial performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is grounded in three theoretical considerations. First, as suggested in previous research (O'Cass et al , 2014), the ambidexterity theory is given focus and emphasis placed on the capability to combine both exploitation and exploration strategies (Foglia et al , 2019). The ambidexterity theory positions that a firm can be ambidextrous when it seeks to align its activities between exploiting existing capabilities while also addressing dysfunctional rigidity through not only renewal but also seeking to replace this (Benner and Tushman, 2003; McCarthy and Gordon, 2011).…”
Section: Theoretical Framework and Hypotheses Proposedmentioning
confidence: 99%
“…Furthermore, publicly funded health-care agendas, which outline clear targets, compliance standards and assurance requirements, are developed externally by central government, and Senior leaders within the health-care system are tasked with their implementation (Donabedian & Bashshur, 2002). As such, though recent research suggests that health-care leaders’ ambidexterity elicits positive outcomes (Cegarra-Sánchez, Cegarra-Navarro, Chinnaswamy, & Wensley, 2020; Foglia, Ferrario, Lettieri, Porazzi, & Gastaldi, 2019), there may be more opportunity and regular need for exploitation activities in this sector. These results reinforce the need to examine ambidexterity in organisations by attending to their unique sector and context, including strategic aims, operations and resource constraints (Mueller et al, 2013).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Such a tension between maintaining the existing services and innovating may be mediated by ambidexterity. Ambidexterity is defined as the ability to both use and refine existing knowledge (exploitation) while creating new knowledge to overcome knowledge-gaps identified in the execution of the work (exploration) (Foglia et al, 2019;Turner et al, 2013). While exploration focuses on experimenting, innovating, and looking for novelty (Lavie et al, 2010), exploitation focuses on recombining current knowledge, abilities to meet needs in changing times, and scarcity of resources (Gastaldi et al, 2018).…”
Section: Characteristics Of the Interventionmentioning
confidence: 99%
“…Within an innovative organization, there may be a seemingly conflicting nature of exploitation of daily activities vs exploration of innovative leads, and this may be partly resolved by individual characteristics and attitudes and other cultural elements. In hospital contexts it has been demonstrated that lead physicians' leadership style as well as organizational creativity plays a key role in materializing ambidextrous behaviors (Foglia et al, 2019). Also, learning behavior has been positively associated with team outcome and innovation (Lavie et al, 2010;Miron-Spektor et al, 2011).…”
Section: Characteristics Of the Interventionmentioning
confidence: 99%